2014
DOI: 10.1002/chem.201405652
|View full text |Cite
|
Sign up to set email alerts
|

Thienoacene‐Fused Pentalenes: Syntheses, Structures, Physical Properties and Applications for Organic Field‐Effect Transistors

Abstract: Three soluble and stable thienoacene-fused pentalene derivatives (1-3) with different π-conjugation lengths were synthesized. X-ray crystallographic analysis and density functional theory (DFT) calculations revealed their unique geometric and electronic structures due to the interaction between the aromatic thienoacene units and antiaromatic pentalene moiety. As a result, they all possess a small energy gap and show amphoteric redox behaviour. Time dependent (TD) DFT calculations were used to explain their uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…Isomeric DTP 3 was also synthesized by Kawase et al [22e] . Since then, the semiconducting properties of organic field‐effect transistors (OFETs) have been intensively studied for several DTP‐containing π‐electron systems, such as conjugated polymers [25] and acene‐like derivatives [5c] . Nevertheless, to our surprise, the effects of the fused thiophene ring on the antiaromaticity of pentalene have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Isomeric DTP 3 was also synthesized by Kawase et al [22e] . Since then, the semiconducting properties of organic field‐effect transistors (OFETs) have been intensively studied for several DTP‐containing π‐electron systems, such as conjugated polymers [25] and acene‐like derivatives [5c] . Nevertheless, to our surprise, the effects of the fused thiophene ring on the antiaromaticity of pentalene have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we found that the fusion of two five‐membered rings onto the zigzag edges of acene molecules resulted in very stable acenes having a small band gap ( B ) as a result of an intramolecular donor–acceptor interaction, as well as kinetic blocking of the reactive zigzag edges . Alternatively, fusion of an anti‐aromatic pentalene unit along the long axis of an acene ( C ) is another way to approach making stable acene‐based materials for applications such as ambipolar organic field effect transistors (OFETs) . However, we believe that a more efficient way for stabilization is to fuse the pentalene unit to the zigzag edges of acene molecules because the HOMO coefficients of acenes mainly localize at the zigzag edges, and thus we hypothesized that Z‐shaped pentaleno‐acene dimers ( D ) would be stable and show dramatically different properties from their respective acene monomers.…”
Section: Figurementioning
confidence: 99%
“…17–19 Importantly, it has been suggested that antiaromaticity can compress the highest occupied molecular orbital (HOMO)–lowest unoccupied molecular orbital (LUMO) energy gap and potentially promote carrier mobility in organic semiconductors, which is desirable for application in a number of organic electronic device classes, 20–22 such as organic solar cells (OSCs) 23,24 and organic field-effect transistors (OFETs). 20,25–28 Through important design contributions both from synthetic and theoretical chemists, diverse antiaromatic molecule classes have been developed, including pentalenes, 29,30 indacenes, 31,32 cyclooctatetraenes, 33,34 and their derivatives. 35–37 However, compared to the literature of aromatic compounds, optoelectronic investigations of antiaromatic materials remain far more limited, primarily due to the modest stability of typical antiaromatic compounds 38 and challenges in their chemically modification, which has typically involved fusion with aromatic rings, 19,39 replacement of C–C bonds with isosteric B–N bonds, 40 and aromatic ring functionalization.…”
Section: Introductionmentioning
confidence: 99%